Magnitude and associated factors of neonatal mortality among neonates admitted at Dessie comprehensive specialized hospital, Northeast, Ethiopia - Adugna, Berhanu; Asaminew, Robel; Maru, Getye Solomon; Eshetie, Haimanot Ayele; Mohammed, Endris; Samuel, Ayele; Mekonnnen, Abdulmelik; Fentaw, Nurye; Belay, Brhanu; Mekonen, Adem; Nigussie, Mengstie; Getaneh, Fekadeselassie Belege; et al. (Frontiers in Pediatrics, 2025)
BackgroundNeonatal mortality rate is high in sub-Saharan Africa than high-income countries in relation to the growing wealth disparity. Different factors are linked with neonatal mortality in Ethiopia. Identification of the causes of death is the first step in reducing mortality rates. Thus, the aim of this study was to assess the magnitude of neonatal mortality and associated factors among neonates admitted in Neonatal Intensive Care Unit (NICU) in Dessie Comprehensive Specialized Hospital, Northeast Ethiopia.MethodsA retrospective cohort study was conducted among 1,598 neonates admitted in Neonatal intensive care unit of Dessie Comprehensive Specialized Hospital from 28/06/2022 to 30/03/2023. Demographic and clinical data were abstracted from admission/discharge registration books; perinatal facility-based data abstraction form and patient medical records using data extraction checklist. Bivariable and multivariable analyses were conducted to determine the factors associated with neonatal mortality and variables with an adjusted relative risk (ARR) and its P-value < 0.05 were considered statistically significant. Model fitness was computed using Hosme-Lemeshow Goodness of fitness (P = 0.847).ResultsAmong 1,598 neonates who were admitted in NICU were included in this study of which 914 (57.2%) were males. The magnitude of neonatal mortality was 10.2%. Prematurity (ARR = 2.58, 95% CI: 1.39–4.87, P < 0.009), sepsis (ARR = 1.47 95% CI: 1.02–2.11, P < 0.036), birth asphyxia (3.59 = 4.36, 95% CI: 2.40–6.87, P < 0.008), and respiratory distress syndrome (ARR = 2.93, CI: 1.47–5.30, P = 0.011) were independent predictors of neonatal mortality.ConclusionThe magnitude of neonatal mortality was 10.2% which alarms the need of immediate collaborative actions for reduction of the burden particularly tackling on the causal factors such as prematurity, sepsis and birth asphyxia which leads adverse birth outcomes. Therefore, maternal counseling, giving focused ante natal care as well as behavior change communications might be considered to promote positive behaviors are recommended to avoid the leading causes of neonatal mortality.